Sexual behavior of mutant strains of the medfly Ceratitis capitata (Diptera: Tephritidae) - Briceño, R D. (2003)
Males of the mutant strains (blind, vestigal-winged) of the Mediterranean fruit fly (medfly), Ceratits capitata (Wiedmann) showed differences in behavior compared with control (mass-reared) males. Mutant males made fewer mating attempts and achieved fewer matings than control males. Vestigal-winged females copulated less frequently with both mutants. Blind males climbed rather than jumped onto females and copulated in very low numbers compared with control and vestigal males. Blind females copulated normally with control, males and in very low numbers with both types of mutant males.